Federative autonomy, municipal education/education systems: impacts for education in Tocantins - Carlos Roberto Jamil Cury; Rosilene Lagares; Ítalo Bruno Paiva Gonçalves (Universidade Federal do Norte do Tocantins, 2021)
In Brazil, there are four types of federal entities endowed with autonomy, two of them from traditional entities (Union and States) and two from recent entities (Federal District and Municipalities), unlike the classic federations in which there is a central political power (Union) and the regional centers of power (states). In the framework of the Federal Constitution of 1988, the Municipality is part of the Federation, with administrative, legislative and political autonomy within the scope of its attributions. In the field of education, the municipal federated entity, in contrast to the historical hierarchical condition, at least formally, achieves autonomy to organize its own teaching/education system, a fundamental feature of the Federal State safeguarded by the Constitution and legislation dealing with the subject. In this article, dialectically correlating society and education, the conditions of Tocantins Municipalities are problematized for the materialization of autonomy and education management, based on theoretical and documentaries' bases and unsystematic observation. These entities face conceptual, cultural, political, administrative, financial, pedagogical and collaboration-related challenges. Therefore, care should be taken to avoid a precarious solution, that of nominees systems, created legally, but without real and effective action.